Člověk 9. až 12. století v Hornomoravském úvalu - Šín, Lukáš, 1979- (2006)
My work focuses on slavonic settlement of geomorfological complex Hornomoravský ravine. I attempt restoration of living strategies in whole slavonic period (9. to 12. century) accordance with archeological and anthropological researches. This work deals with restoration ways of agricultural and stallion strategies, making tools, building-up dwelling houses and fortification or funeral ordinance.